Effect of extra-concentrate and probiotics supplementation in peri parturient goat on its milk composition and somatic cell count (Indian Journal of Animal Production and Management, 2024)
Present study was conducted to study the effect of extra concentrate supplementation with or without  probiotics on milk composition and somatic cell count of goatsduring two months of periparturient period.  Twenty four pregnant healthy Boar x local cross dose in the last month of gestation (day 120) were  selected randomly and allotted to 4 groups (T1, T2, T3 and T4) of six animals. The dose were maintained  under stall feeding conditions and offered a daily ration consisting of oats hay @ 1.2 kg/head/day and  commercial pelleted feed @ 577.5 g/head/day. Dose in treatment groups T1 were offered normal daily  ration without supplementation. In T2 group were offered normal ration and extra concentrate @ 150 gram  /head/day, T3 group were offered normal ratio and extra concentrate @ 150 gram/head/day with probiotic  (Saccharomyces cerevisiae x1010 CFU) @ 2.5 gram/head/day and in T4 groups were offered normal ratio  and extra concentrate 150g + probiotic (Saccharomyces cerevisiae x1010 CFU) @ 4 gram/head/day. Milk  samples were collected in the morning of 20th day of lactation and were analyzed for fat, protein, solid not-fat, total solids percent and somatic cell count using standard procedures. There was non-significant  differences (p
Keywords: Concentrate; Milk composition; Periparturient period; Probiotics; Supplementation; SCC